(untitled) - Carne, Paul (Cambridge, UK, 2000)
This new title contains eight complte practice tests for the Cambridge First Certificate in English examination.
Keywords: English language,English language,English language,Test of english as a foreign language; Examinations,Study guides,Study and teaching,Textbooks for foreign speakers,Study guides